2000
DOI: 10.1103/physrevlett.85.3353
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Impact Ionization Cross Section Measurements Out of the52PExcited State of Rubidium

Abstract: We describe new techniques involving trapped atoms as targets for measurements of electron-impact ionization cross sections out of an excited level. By directly detecting the ions formed by electron collisions, we have obtained the first experimental ionization cross sections out of the 5(2)P excited level in rubidium at energies from 40 to 300 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Most EII studies have involved ground states [1,2]. Only a handful of EII studies have been carried out on excited states, and those only spanning a small range of low principal quantum number n in different targets, viz., rare gases [3], some alkaline earths [11], and alkali metals [12,13]. These studies have revealed a shift of the peak in EIICS to lower electron energies with increasing n and enlarged maximum values, corresponding to decreasing ionization energies [3].…”
mentioning
confidence: 93%
“…Most EII studies have involved ground states [1,2]. Only a handful of EII studies have been carried out on excited states, and those only spanning a small range of low principal quantum number n in different targets, viz., rare gases [3], some alkaline earths [11], and alkali metals [12,13]. These studies have revealed a shift of the peak in EIICS to lower electron energies with increasing n and enlarged maximum values, corresponding to decreasing ionization energies [3].…”
mentioning
confidence: 93%
“…In 'conventional' experimental studies performed by measuring the total flux of ions, the primary reasons for the scatter of data are the large uncertainty of the evaluation of the target vapor density and of the total number of ions created in the collision region. Developed during the last two decades, more sophisticated techniques deal with either the high impact energy regime [8,9,17] or the differential cross sections [18,19] and, therefore, cannot improve significantly the general situation.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly sophisticated techniques, both experimental and theoretical, are being applied to meet the demands of basic research and high-technology industry. In this work the trap-loss technique, first developed by Lin and co-workers [1][2][3], is used to determine total cross sections from the fluorescence decays of the trapped atoms, with and without an electron beam present. The loss of atoms from the trap, due to electron collisions, is related directly to the cross section and electron flux through the trap.…”
Section: Introductionmentioning
confidence: 99%